2000
DOI: 10.1002/(sici)1097-4636(20000615)50:4<605::aid-jbm17>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Initial stability of a new hybrid fixation hip stem: Experimental measurement of implant-bone micromotion under torsional load in comparison with cemented and cementless stems

Abstract: A new hybrid fixation stem, named cemented-locked uncemented (CLU), for total hip arthroplasty was developed to achieve good initial stability. Primary stability is guaranteed by the cement which is injected into two pockets in the lateral area. This leaves a large surface available for long-term biologic fixation (direct bone attachment on implant). This study evaluates in vitro the initial stability of the CLU prototype under torsional load, in comparison with cemented and cementless stems. The results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 46 publications
1
21
0
1
Order By: Relevance
“…However, there is no consensus in the literature as to how the femur should be loaded in vitro. Some studies restrictively examine the torsional stability of femoral stems by applying a pure torque moment to the prosthetic head (Gustilo et al, 1989;Nunn et al, 1989;Sugiyama et al, 1989;Phillips et al, 1990;Baleani et al, 2000). In other cases, only the resultant hip contact force has been considered and was directly applied at the prosthesis head, leading to bending and eventually to torsion of the implant (Gebauer et al, 1989;McKellop et al, 1991;Berzins et al, 1993;B .…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no consensus in the literature as to how the femur should be loaded in vitro. Some studies restrictively examine the torsional stability of femoral stems by applying a pure torque moment to the prosthetic head (Gustilo et al, 1989;Nunn et al, 1989;Sugiyama et al, 1989;Phillips et al, 1990;Baleani et al, 2000). In other cases, only the resultant hip contact force has been considered and was directly applied at the prosthesis head, leading to bending and eventually to torsion of the implant (Gebauer et al, 1989;McKellop et al, 1991;Berzins et al, 1993;B .…”
Section: Discussionmentioning
confidence: 99%
“…The behaviour of the Anca DualFit stem has been extensively tested preclinically [2,5,20,23]; load transfer, primary stem stability, and long-term performance (including fatigue damage of the cement) under severe loading, have been investigated in vitro and very good results were found (micromotions never exceeded 80 microns). The mid-term clinical results seem to confirm the in vitro findings.…”
Section: Discussionmentioning
confidence: 99%
“…In active or heavy osteoporotic patients, the ideal fixation could be a hybrid fixation with the best features from both fixation techniques already in use. A partially-cemented hip stem (Anca DualFit, Wright, Arlington, TN, USA) was derived from a successful anatomical cementless design already in use in clinical practice (AncaFit, Wright) and was then validated extensively preclinically [2,5,20,23]. Primary stability is achieved by press-fitting the stem into the femoral canal as for a standard cementless stem, and pressurising bone cement into two pockets in the metaphyseal region of the stem.…”
Section: Introductionmentioning
confidence: 99%
“…From an experimental point of view, Baleani et al quantified boneimplant micromotions under torsional load with position transducers in a hip implant model. A maximum of 56 μm was measured in uncemented stems [1]. Finally, with in vivo models, Jasty et al found that micromotions lower than 40 μm favor bone formation in dog, while micromotions higher than 100 μm lead to the creation of a fibrous tissue [10].…”
Section: Introductionmentioning
confidence: 99%